Chemical profiling of Dioscorea septemloba by High Performance Liquid Chromatography Coupled to Electrospray Ionization and Quadrupole Time-of-Flight Mass Spectrometry. (17th July 2020) - Ling, Yun; Chen, Lu; Wang, Dan; Xiao, Xin; Xu, Wenjing; Yan, Hui; Yu, Hongling; Zhang, Qing; Qu, Weihong; Chen, Jian; Ji, Xiaohong; Yu, Qunying
Abstract: The rhizomes of Dioscorea septemloba (DS) is one of traditional Chinese medicine, which can be used for treatments of urethral and renal infections, as well as rheumatism. Nevertheless, detailed information on DS chemical compositions is still scarce. Therefore, the present work is aimed at investigating the phytochemical components of DS using high performance liquid chromatography coupled to electrospray ionization and quadrupole time-of-flight mass spectrometry in negative ion mode. The proposed method provided tentative identification of 32 components, 6 of which were determined to be new. The present study highlighted the importance of DS as a promising source of medicinal ingredients and provides valuable information on the new potential components in DS.